«ΟΙ ΠΟΠΟΛΑΡΟΙ ΑΠΕΙΛΟΥΝ ΣΙΚΕΛΙΚΟΥΣ ΕΣΠΕΡΙΝΟΥΣ» ΚΕΡΚΥΡΑ 1633-1644 - ΑΡΒΑΝΙΤΑΚΗΣ, ΔΗΜΗΤΡΗΣ (Eoa kai Esperia, 2000)
In the period between 1633 and 1644 Venice was being summoned by the popolariand the contadini of Corfu to establish a new institution: that of the "people'sadvocates and defenders". Their aim was to meet the arbitrariness of the cittadini-the members of the Comunità.Although initially the Venetian Reggimento of Corfu favoured their request, thecittadini'?, severe reaction, especially between 1642 and 1644 when the developmentsculminated, led Venice to abolish the institution. This final decision is undoubtedlyrelated to Venice's general reluctance to reform the administrative structure.Acceptance of the new institution could have led to a "dualism of authority" on theisland, as such an institution would work as an unofficial pole of authority, opposingthe Comunità'?, formal mechanism.This study aims to clarify these events, but also to connect the developments onCorfu with the equivalent ones on Zante, between 1628 and 1632. The analogies andsimilarities of these two cases constitute evidence for a common crisis in thecredibility of the administration system on the Ionian Islands in the early 17thcentury; a crisis in direct relation to the activity of the cittadini and the objectives ofthe popolari. In this context it would prove extremely useful to analyze certainparameters of the issue: a) the extent to which the institutions correspond to thesocial developments, b) the emergence of a new mentality among the city's popularorders and c) the formation stages of a popular ideology.